ANALISIS KETEPATAN PEMBERIAN KODE DIAGNOSA DAN TINDAKAN TERHADAP PEMBAYARAN KLAIM JKN RAWAT INAP DI RSUP DR. HASAN SADIKIN BANDUNG - Intan Pujilestari (Jurnal TEDC, 2020)
Based on the result study conducted by authors in the sub-installation of coding part of inpatient in RSUP Dr. Hasan Sadikin Bandung 7 January until 10 January year 2020 was conducted sampling as many as 61 files taken from the correction file BPJS which is returned back by the Verificator in September 2020. Authors found the number of precision encoding diagnosis of 22 sample correction files with presentation (36%), and the inaccuracy number of the encoding of diagnosis of 39 correction files with presentation (64%). The method used in this research is a quantitative method with a descriptive approach. The population in the study was a correction file of JKN Inpatient claims in October 2019 as many as 95 files with quota sampling techniques. The data collection techniques used are observation techniques, interview techniques, and literature studies. The results showed that there was precision of codification and action was 63 claims of file correction or with a total percentage of 66.31% and the amount of codification inaccuracy and action was as many as 32 claims of file correction or with a total percentage of 30.68%. The author advises the SOP (standard operational procedure) to be immediately signed by the President Director in order to be a legal, as well as a regular and periodical socialization of the practitioner on how important the writing of complete, precise and accurate medical records and to coordinate or supply to all stakeholders such as doctors, coder, billing personnel, workshops on the rules of claim.